Lauserakenteen kuvaamisesta I - Sammallahti, Pekka (Virittäjä, 2002)
Describing sentence structure (englanti) 1/2003 (107) Describing sentence structure In this two-part article, the writer develops a general descriptive model of sentence structure based on a branching dependency hierarchy of linguistic elements (morphemes and/or words) and their semantic relations (semantic function, semantic connection and semantic role), and the mapping of two-dimensional sentence structures into linear uttered or written sentences. In a dependency hierarchy semantic function operates between the head and the dependent and/or between the codependent and the dependent, and takes the dependent as its value. Applying the general model to the description of Finnish, twelve semantic functions are posited: modification, categorization, determination, quantification, complementation, predication, positioning, actuation, substantiation, estimation, inclusion and focusing. The first seven of these, or their equivalents, are widely employed in linguistic description. A further semantic function in many languages is negation, but this is not so in Finnish, which traditionally has only sentence truth-value negation, expressed by a negative finite verb-form functioning as head of the sentence. Semantic connection describes the different semantic functions of a dependent in relation to its head and its codependents: (a) rectives are dependents which have a semantic function in relation to the head only; (b) oblicutives have semantic functions in relation to both the head and one of the codependents; and (c) adjunctives have a semantic function in relation to the totality of the head and the codependents. Semantic role can be defined as the role of a dependent in the state of affairs expressed by its head, usually a verb. Twenty different semantic roles are presented. Twelve of these are widely used in linguistic description (since Charles J. Fillmore, 1968): theme, agent, instrument, result, patient, experiencer, benefactive, possessor, goal, path, source and location. The other semantic roles defined and explained are mover, changer, owner, donor, conveyer, recipient, association and context. Semantic roles are confined to elements expressing entities (both concrete and abstract, and states of affairs, etc.), whereas semantic functions may additionally have elements expressing properties (qualities, quantities, etc.) as their values. An important criterion in distinguishing sentence parts from each other is their ability or inability to be linked by a coordinating conjunction. It is argued that semantic relations should be used as the primary criteria in sentence structure analysis, and therefore that formal properties should not be considered primary but secondary criteria. It is also argued that having structural descriptions based on semantic criteria allows for improved comparability of structures across languages, and hence a firmer basis for research in linguistic typology and change. The writer discusses a number of problems in Finnish syntax on the basis of the proposed model, and offers new solutions to these problems. A tentative taxonomy of Finnish sentence parts is given as an appendix (in Finnish). The model represents a further step away from the principles of the minimalist programme within generative grammar, which has remained a prisoner of its own notational system. Instead, it aspires to attain the ideals for language description set by Paul Kiparsky (1968), by abandoning movement transformation and separate categorial nodes such as NP, AdjP, PP in structural descriptions. It also dismisses the categorial tree diagram used so far in all versions of generative grammar as inadequate for the description of word order in many languages, including Latin and Dyirbal. Pekka Sammallahti